Occurrence of highly radioactive microparticles in the seafloor sediment from the pacific coast 35 km northeast of the Fukushima Daiichi nuclear power plant. (March 2021) - Ikenoue, Takahito; Takehara, Masato; Morooka, Kazuya; Kurihara, Eitaro; Takami, Ryu; Ishii, Nobuyoshi; Kudo, Natsumi; Utsunomiya, Satoshi
Abstract: To understand the properties and significance of highly radioactive particles in the marine environment, we have examined seafloor sediment with a radioactivity of ∼1200 Bq/kg (dry weight; after decay correction to March 2011) collected 35 km northeast of the Fukushima Daiichi Nuclear Power Plant (FDNPP). Among the 697 highly radioactive particles separated from the sediment, two particles, D1-MAX and D1-MID, had a total Cs radioactivity of ∼56 and 0.67 Bq (after decay correction to March 2011), respectively. These particles were characterized with a variety of electron microscopic techniques, including transmission electron microscopy. The 134 Cs/ 137 Cs radioactivity ratio of D1-MAX, 1.04, was comparable to that calculated for Unit 2 or 3. D1-MAX consisted mainly of a Cs-rich microparticle (CsMP) with a silica glass matrix. The data clearly suggested that D1-MAX resulted from a molten core–concrete interaction during meltdowns. In contrast, D1-MID was an aggregate of plagioclase, quartz, anatase, and Fe-oxide nanoparticles as well as clay minerals, which had adsorbed soluble Cs. D1-MID was likely a terrestrial particle that had been transported by wind and/or ocean currents to a site 35 km from the FDNPP. The radioactive fractions of D1-MAX and D1-MID were 15% and 0.36%, respectively, of the total radioactivity in the bulk sediment. These highly radioactive particles have a great impact on the movement of radioactive Cs in the marine environment by carrying condensed Cs radioactivity with various colloidal and desorption properties depending on the host phase. Highlights: Two highly radioactive particles were isolated from Pacific Ocean sediments. Total Cs radioactivities of the two particles were ∼56 and 0.67 Bq. The physicochemical properties of the two particles were characterized. Processes by which the particles were transported 35 km from shore were estimated. Such particles may account for much of the movement of radiocesium in the ocean.